2006
DOI: 10.1158/1055-9965.epi-05-0554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urinary 15-F2t-Isoprostane and 8-Oxodeoxyguanosine Levels and Breast Cancer Risk

Abstract: To evaluate the role of oxidative stress in breast cancer, we measured urinary levels of 15-F 2t -isoprostane (15-F 2t -IsoP) and 8-oxodeoxyguanosine (8-oxodG) in 400 cases and 401 controls, participants of the Long Island Breast Cancer Study Project. We also analyzed the effect of different factors that are associated with oxidative stress and might influence 15-F 2t -IsoP and 8-oxodG levels. We observed a statistically significant trend in breast cancer risk with increasing quartiles of 15-F 2t -IsoP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 52 publications
11
87
0
Order By: Relevance
“…In a population-based case-control study of 400 cases and 401 controls from the Long Island Breast Cancer Study Project, a positive association was reported for urinary 15-F 2t -IsoP measured via immunoassay and risk of breast cancer, but not urinary 8-oxodG measured by competitive enzyme-linked immunosorbent assay (ELISA). 40 All samples for the cases were collected within on average 3 months after diagnosis of breast cancer, with most before the initiation of chemotherapy. The positive association between 15-F 2t -IsoP and increased risk of breast cancer was found among both pre-and postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…In a population-based case-control study of 400 cases and 401 controls from the Long Island Breast Cancer Study Project, a positive association was reported for urinary 15-F 2t -IsoP measured via immunoassay and risk of breast cancer, but not urinary 8-oxodG measured by competitive enzyme-linked immunosorbent assay (ELISA). 40 All samples for the cases were collected within on average 3 months after diagnosis of breast cancer, with most before the initiation of chemotherapy. The positive association between 15-F 2t -IsoP and increased risk of breast cancer was found among both pre-and postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…Lovaza administration, on the other hand, did not influence IGF-I levels as also observed by Yee et al 15 Whether increased oxidative stress, inflammation and preferential estrogen metabolism toward the pro-carcinogenic 16-a-hydroxylated metabolite have a role in breast cancer development remains uncertain at this time in view of conflicting reports in the literature. [23][24][25] With regard to the role of oxidative stress and inflammation, a major issue is the appropriate selection of the most relevant biomarkers. Therefore, the lack of an effect of our interventions on select biomarkers of inflammation and oxidative stress does not necessarily rule out a role of cellular stress and inflammation on breast cancer development or an antitumor action of our combined treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical and experimental findings suggest that oxidative stress is associated with the progression of breast cancer. [3][4][5][6] Thus, it is very important to identify the biological effects of the antioxidant compounds, such as PDTC, to antagonize the deleterious action of ROS related to carcinogenesis and cancer progression. A recent study showed that intravenous administration of PDTC reduced tumor growth in nude mice using MCF-7 sphere cells as model of breast cancan stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent clinical and experimental findings suggest that oxidative stress is associated with the progression of breast cancer. [3][4][5][6] Oxidative damage of DNA has been implicated in the initiation of mammary tumors. [7][8][9] Aside from the role of oxidants in the induction of mutation, oxidative stress also mediates cell signaling pathways involved with increasing mutation rate, activating growth-promoting signaling pathways, stimulating tumor angiogenesis, and accelerating tumor progression.…”
Section: Introductionmentioning
confidence: 99%